Analisa Komparatif Prediksi Financial Distress Dengan Metode Altman Z-Score Dan Grover O-Score Pada PT. Bank Panin Syariah - Trisnia Widuri (Universitas Islam Kadiri, 2018)
This study compares the accuracy of the model in predicting the financial condition of a company's distress. The models that will be used in this study are the Altman Z-Score model and the Grover O – Score model. This is because there is a contra about the accuracy of the two models in predicting financial distress of a company. The sample used in this study is PT. Bank Panin Dubai Syariah, Tbk. From 2013 to 2017, the results stated that the Altman Z – Score model was better at predicting a company's financial distress compared to the Grover O – Score.